Alleviating effects of probiotic supplementation on biomarkers of inflammation and oxidative stress in non-communicable diseases: a systematic review and meta-analysis using the GRADE approach - Xiaoyuan Yu; Li Yan; Lingxiao Chen; Xianmei Shen; Wenzheng Zhang (BMC Pharmacology and Toxicology)
Abstract Background Inflammation and oxidative stress are key risk factors in noncommunicable diseases (NCDs). Probiotics have been suggested to be beneficial in mitigating inflammation and oxidative stress; however, the evidence remains inconsistent due to variations in study design, dosage, and patient populations. Methods Studies were included following a systematic search of PubMed, Scopus, Cochrane Library, Web of Science, and EMBASE, provided they fulfilled the eligibility criteria. This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to clarify the effects of probiotics on oxidative stress and inflammation in non-communicable diseases (NCDs). Results A review of 18 studies revealed that probiotic supplementation significantly reduced CRP (SMD = -1.33, 95% CI: -1.84, -0.82; p < 0.001, high certainty), TNF-α (SMD = -1.10, 95% CI: -1.66, -0.55; p < 0.001, low certainty), and MDA levels (SMD = -1.38, 95% CI: -2.08, -0.69; p < 0.001, high certainty). Additionally, while probiotics increased GSH levels (SMD = 0.65, 95% CI: 0.06, 1.23; p < 0.001, high certainty), they did not change the levels of IL-6 (SMD = -1.05, 95% CI: -2.21, 0.11; p < 0.001, low certainty), NO (SMD = 0.47, 95% CI: -0.54, 1.48; p = 0.363, low certainty) and TAC levels (SMD = 0.24, 95% CI: -0.27, 0.74; p = 0.357, moderate certainty). Conclusion The supplementation of probiotics may have mitigated biomarkers associated with inflammation and oxidative stress.